2018
DOI: 10.1177/155892501801300106
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Knitted Fabrics Finished with Different Silicone Softeners

Abstract: Silicone softeners make fabric soft, brilliant, greasy and more elastic, resulting is acceptable handle. In this research work, the effect of using different silicone softeners on pilling resistance and on some physical and mechanical properties of knitted fabrics was evaluated. Industrially applied silicone softeners of three different types (macro, semi-micro, micro) were used on fabrics knitted from different fiber materials (Egyptian cotton, Tencel LF, Tencel STD, bamboo, Modal and Micro-modal). The influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
7
0
3
Order By: Relevance
“…Pilling is a critical problem in daily clothing, especially for wool materials. Pilling not only deteriorates the appearance and comfort of the fabric but also reduces the service life of the textile product. , The pilling properties of wool fabrics are mainly influenced by the inter-fiber friction in the fabric. To examine the antipilling mechanism of the EWNS technology, a single fiber friction coefficient test and micro characterization were implemented. First, the coefficients of friction were measured using the capstan method.…”
Section: Resultsmentioning
confidence: 99%
“…Pilling is a critical problem in daily clothing, especially for wool materials. Pilling not only deteriorates the appearance and comfort of the fabric but also reduces the service life of the textile product. , The pilling properties of wool fabrics are mainly influenced by the inter-fiber friction in the fabric. To examine the antipilling mechanism of the EWNS technology, a single fiber friction coefficient test and micro characterization were implemented. First, the coefficients of friction were measured using the capstan method.…”
Section: Resultsmentioning
confidence: 99%
“…Igarashi and Nakamura (2019) identified that the main mechanism of softening is because of the prevention of cross-linkage of the fiber with the inbound water in the fabric. All other identified recent literature works are performed mainly on the other softening chemicals such as silicones and resins and their influence on the fabric properties and friction characteristics (Badr, 2018;Naima et al, 2018;Zięba et al, 2019).…”
Section: Effect Of Rinse Cycle Softener Treatment 199mentioning
confidence: 99%
“…Küçük partiküllere sahip nano ve mikro silikon emülsiyonları lif yüzeylerine penetre olarak kumaşlara, iyi bir iç yumuşaklık ve buruşmazlık özellikleri kazandırırken, daha büyük partiküllere sahip olan makro emülsiyonlar ise yüzey yumuşaklığı sağlamaktadır [2,5]. Literatür incelendiğinde, farklı partikül büyüklüğüne sahip silikon yumuşatıcıların kumaşların çeşitli performans özellikleri üzerindeki etkisinin araştırıldığı birçok çalışmanın mevcut olduğu; ancak mikro ve makro silikon yumuşatıcıların farklı karışım oranlarının etkisinin incelenmediği görülmüştür [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Bu nedenle, bu çalışmada, farklı oranlarda karıştırılmış mikro ve makro silikon yumuşatıcıların, kumaşların mekanik performansı ve beyazlığı üzerindeki etkisi araştırılmıştır.…”
Section: Introductionunclassified
“…Terbiye işlemlerinde, yardımcı madde kullanımının % 65'i bitim işlemlerinde gerçekleşirken, bunun da yaklaşık %30'una karşılık gelen büyük bir bölümünü, yumuşatıcı madde kullanımı oluşturmaktadır [2]. Yumuşatıcı madde kullanımında amaç, ön terbiye işlemleri sırasında uzaklaştırılan ve life yumuşak tutum veren, doğal liflerin yapısında bulunan yağ, mum, pektin gibi maddeler ile sentetik liflerin üretimi esnasında verilen preparasyon maddelerinin uzaklaşması nedeniyle kaybedilen yumuşak tutumu kumaşa yeniden kazandırmak ve hatta başlangıçtaki yumuşaklığı daha da geliştirmektir [2,4,5]. Yumuşatıcı maddeler sayesinde, tekstil ürünü hem güzel bir tutum, esneklik, dolgunluk, dökümlülük kazanmakta hem de aşınma dayanımı, boncuklanma, statik elektriklenme, buruşma, giyim konforu, dikiş kolaylığı gibi özellikleri olumlu yönde gelişmektedir [5][6][7][8][9].…”
Section: Introductionunclassified
See 1 more Smart Citation